Tourists' emotional changes and eWOM behavior on social media and integrated tourism websites. (20th November 2019) - Zhou, Simin; Yan, Qiang; Yan, Mengling; Shen, Chuwen
Abstract: Electronic word of mouth (eWOM) has become increasingly important for the tourism industry. However, existing studies tend to overlook tourists' eWOM sharing behavior, especially on different platforms. This paper aims to explore the antecedents of distinct eWOM behaviors on social media platforms and integrated tourism websites. Thirty tourists with rich travel experience were invited to attend in‐depth interviews. Tourists' emotions, eWOM motivations, and platform features were explored by coding. Based on dramaturgical theory and task–technology fit theory, we discovered the ways that platform features fit with tourists' eWOM motivations, which provide important implications for destination and platform management.